Annual digest of human rights judgements 2000 - "Antony, M. J" (New Delhi, 2001)
The Supreme Court of India and the high courts have delivered scores of judgments in the year 2000 which deal with different aspects of civil liberties and human rights of the citizens and even foreigners. This is a compilation of the summaries of such judgments, arranged topic-wise. The subjects cover a large field. For instance, hundreds of persons are in prisons, desperately waiting for their trial to begin when the prosecution proceedings have not even moved an inch.
Keywords: Human rights-Judgement-2000